Die Berliner Mauer und ihre Projektionen: Die Inferenzstruktur des politischen Diskurses der Aktionsseite Erster Europäischer Mauerfall des Zentrums für Politische Schönheit (Altre Modernità, 2021)
The discourse of political activism makes use in many cases of an intertextual rereading of historical events for purposes of discussion. This is the case of the action of the Zentrum für Politische Schönheit Erster Europäischer Mauerfall, which took place in Berlin in 2014. The action evokes the Berlin Wall and its fall in a prototypical way to project its political discourse on all the walls currently present in the world and on the consequences of their existence for some political minorities. This contribution, remaining within the theoretical horizon of digital multimodality, intends to focus on the pragmatic and linguistic strategies recurring in this action, identifying the different plans for constructing the discourse and the numerous visual linguistics conflicts essential to the communication of contents.